Novel lateral whole‐body dual‐energy X‐ray absorptiometry of lumbar paraspinal muscle mass: results from the SarcoSpine study. Issue 4 (28th May 2021) - Lee, Sang Yoon; Kim, Dong Hyun; Park, Sang Joon; Park, Jinhee; Chung, Sun Gun; Lim, Jae‐Young
Abstract: Background: Here, we aimed to propose novel lateral whole‐body dual‐energy X‐ray absorptiometry (lateral DXA) as a simple tool for measuring spinal muscle mass and investigate the feasibility of lateral DXA to measure lumbar paraspinal muscle (LPM) mass compared with lumbosacral spine three‐dimensional magnetic resonance imaging (3D MRI). Methods: Twenty consecutive participants were enrolled from a prospective observational cohort (SarcoSpine study). Lateral DXA was scanned with each participant in the lateral decubitus position. The region of interest was defined to analyse the LPM mass. LPM total volume, LPM cross‐sectional area at the L3 mid‐vertebra and L4/5 mid‐disc levels and each signal intensity were measured by 3D MRI. Isokinetic and isometric back extensor muscle strengths as well as back extensor endurance were examined. The correlation between lateral DXA‐based mass (weight) and 3D MRI‐based LPM volume was analysed. Results: The mean age of the 20 participants (15 women, 5 men) was 72.2 ± 4.9 years. LPM mass by lateral DXA was positively correlated with LPM volume by 3D MRI (β = 0.333, r = 0.692, p < 0.001) and negatively correlated with signal intensity of the total LPM (β = −0.263, r = −0.530, p = 0.016). LPM mass was also correlated with appendicular limb muscle mass, handgrip strength and gait speed as well as back extensor endurance ( r = 0.620, p = 0.004). Conclusions: Our data suggest that LPM mass assessed by lateral DXA was positively correlated with LPM volume by 3D MRI in older adults. Lateral DXA may be a potential substitute for the cross‐sectional area measurement of LPM mass. Further studies are required to validate this lateral DXA technique.